2021
DOI: 10.17129/botsci.2654
|View full text |Cite
|
Sign up to set email alerts
|

Breeding system in a population of the globose cactus Mammillaria magnimamma at Valle del Mezquital, Mexico

Abstract: Background: The breeding system of Mammillaria magnimamma was initially described as hermaphroditic. However, some individuals in a natural population at Valle del Mezquital exhibited a seemingly non-functional androecium. Objectives: To determine the breeding system of M. magnimamma through morphological characterization of floral types. Study site and years: The study was conducted at Valle del Mezquital, Mexico, during the 2019 reproductive season. Methods: We characterized floral polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…This study demonstrated that the natural populations of pitahaya from the five departments showed high variation in the morphological characteristics that were evaluated in situ. Although the five studied sites have similar climatic conditions, the same variables should be evaluated in accessions established in a single environment, thereby confirming whether the variation might have been affected by uncontrolled environmental factors in this observational study, such as different soil types [29]. Studies in other countries have found high variation in characteristics of agronomic importance, even within the same species of Hylocereus spp.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This study demonstrated that the natural populations of pitahaya from the five departments showed high variation in the morphological characteristics that were evaluated in situ. Although the five studied sites have similar climatic conditions, the same variables should be evaluated in accessions established in a single environment, thereby confirming whether the variation might have been affected by uncontrolled environmental factors in this observational study, such as different soil types [29]. Studies in other countries have found high variation in characteristics of agronomic importance, even within the same species of Hylocereus spp.…”
Section: Discussionsupporting
confidence: 64%
“…[6,8,20], which is favorable for future breeding studies. The availability of this information would be of great assistance in developing an appropriate method for the cultivation of a particular species [29,30]. Several studies related to the diversity of dragon fruit have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recent works focused on widespread cactus species have revealed mating and breeding system variations as a result of eco‐geographic heterogeneity (e.g. Pachycereus pringlei (Gutiérrez‐Flores et al 2017), Mammillaria magnimamma (Callejas‐Chavero et al 2021)), but the link between pollinator availability and among‐population variation in mating systems has not been explored. The closest approximation is a study between two sympatric Opuntia species that differ in their mating systems, which found that the self‐incompatible O. polyacantha attracts twice as many species of visitors as does the self‐compatible O. phaeacantha , probably due to its longer flowering time, larger flowers and the greater nutritional value of its nectar (Osborn et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In Colombia, morphological, molecular, and biochemical characterization studies are scarce [3]; most studies have been focused on the physiological component of seeds for in vitro propagation and on the identification of limiting pathogens in production, among others [12][13][14][15]. Morphological and molecular characterization studies carried out on the germplasm at the Department of Boyacá have shown that there is genetic diversity in the province of Lengupá, which is the basis for the establishment of any selection process that would identify elite materials that respond to the needs of the farmer, producers, and consumers.…”
Section: Introductionmentioning
confidence: 99%